2022
DOI: 10.1002/smll.202106719
|View full text |Cite
|
Sign up to set email alerts
|

A Ternary Molten Salt Approach for Direct Regeneration of LiNi0.5Co0.2Mn0.3O2 Cathode

Abstract: metals and organic electrolytes, which are hazardous to the environment.Apparently, recycling spent LIBs is a far-sighted strategy for both resource recovery and environmental protection. Particularly, re-utilizing the cathode materials is the primary task for battery recycling since they make up approximately 35% of the cost and contain abundant valuable metals. [4] Conventional approaches to recycle cathodes are based on the hydrometallurgy [5] and pyrometallurgy [6] processes, which are either tedious or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 41 publications
3
70
0
Order By: Relevance
“…In order to achieve closed-loop recycling, a ternary molten salt strategy was adopted for direct regeneration of the lithium nickel cobalt manganese oxide (LiNi 0.5 Co 0.2 Mn 0.3 O 2 , NCM523) cathode. 42 The XRD pattern of regenerated NCM (denoted as R-NCM) is displayed in Fig. S7a †.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve closed-loop recycling, a ternary molten salt strategy was adopted for direct regeneration of the lithium nickel cobalt manganese oxide (LiNi 0.5 Co 0.2 Mn 0.3 O 2 , NCM523) cathode. 42 The XRD pattern of regenerated NCM (denoted as R-NCM) is displayed in Fig. S7a †.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement results revealed that the regenerated LiNi 0.5 Co 0.2 Mn 0.3 O 2 cathode materials delivered a reversible capacity of 160 mAh g -1 at 0.5 C with retention of 93.7% after 100 cycles, which is compared favorably to the fresh ones, indicating the effectiveness of this ternary molten salt system to directly regenerate the degraded cathode materials. [159] Yang and co-workers also reported a ternary eutectic system of LiOH-KOH-Li 2 CO 3 to restore the electrochemical performances of degraded LiCoO 2 cathode materials in the air atmosphere. [158] A "dissolution-recrystallization" mechanism was proposed to elucidate the regeneration process, in which the LiOH-KOH-Li 2 CO 3 molten salt with abundant Li + , homogeneous thermal circumstance, suitable dissolving capacity, and high ion diffusion rate should facilitate the compensation of Li + deficiencies, decomposition of impurities and final renovation of damaged structures.…”
Section: Eutectic Methodsmentioning
confidence: 99%
“…Moreover, the direct regeneration process in molten salt mixture can be carried out at an ambient pressure, in a sharp contrast with the high-pressure conditions applied in hydrothermal solution, which further increases its convenience and universality for regenerating cathode materials. [156][157][158][159] Note that, the peeled cathode materials from retired LIBs in an industrial process usually contain impurities, such as PVDF binders, carbon-based conductive agents, etc. [67,71,160] It is significant to realize the direct renovation of degraded cathode materials in such a complex system for the large-scale production.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Molten eutectic salts can be used as a re-lithiation reagent, via provision of low temperature, ambient pressure, and liquid environment for regeneration. [176][177][178][179][180][181][182][183] Eutectic molten salts, including LiOH-LiNO 3 , LiOH-Li 2 CO 3 and KCl-KNO 3 -LiNO 3 have been used in regeneration of NCM523 material which exhibited significant performance. [176][177][178] Molten salts, including Li 2 SO 4 -LiOH for single-crystal Ni-rich NCM, 179,180 and LiOH-KOH-Li 2 CO 3 for LiCoO 2 , and LiOH-LiNO 3 for NCM111 and LMO, are reported.…”
Section: Direct Recyclingmentioning
confidence: 99%